The Influence of Hurdle Drill and Zig Zag Running Training Models on Agility at PFK Angels Football Club - Maghfiroh, Imroatul; Yusuf, Jamaludin; Risdiani, Risdiani; Putri, Mega Widya (JUMORA: Jurnal Moderasi Olahraga, 2023)
This study aims to examine: the effect of the hudle drill and zig zag running training models on agility; whether there is an influence of the hurdle drill training model on agility; and whether there is an effect of the zig zag running training model on agility. This research method uses quasi-experiments and the research population is all PFK Angels club players with research samples taken using the total sampling method, so that the research sample is 16 players. The instrument for measuring agility uses the Illimois Agility Test. The data analysis technique used is the T-Test at a significance level of ? = 0.05. The results of the study are as follows: (1) There is a significant effect of the hurdle drill and zig zag running training model on agility because the p significance is 0.270 > 0.05 for the pretest and the p significance value is 0.202 > 0.05. (2) there is an effect of the hurdle drill training model on agility because the significance value of p is 6.000 > 0.05 for the pretest and for the posttest the significance of p is 0.001 < 0.05 these results show a significant difference. (3) there is an effect of the zig zag running training model on agility because the p significance value is 3.586 > 0.05 for the pretest and for the posttest the p significance is 0.009 <0.05 these results show a significant difference.   Keywords: Hurdle Drill, Zig Zag, Agility